Abrasive resistance and microhardness of self-adhesive (Surefil one) and conventional bulk fill composites: An- in vitro study. - Maryam Fakher Ibrahim; Bahar Jafaar Selivany; Abduloma Baraka Ali (Erbil Dental Journal)
Aims and objectives To evaluate abrasive resistance and microhardness of self-adhesive Surefil one and conventional bulkfill composites Beautifil bulk restorative and Filtek one bulk fill restorative. Materials and Methods: For the abrasive resistance test, thirty composite discs (4 mm hieght×8 mm width) in each group (n=10) were fabricated. GI: Beautifil bulk restorative, GII: Filtek One Bulk fill restorative and GIII: Surefil one self-adhesive. By placing the material in a mold in a single increment then curing. A custom-made toothbrush simulator was employed for wear testing. The samples weighted before and after the brushing to measure the weight loss. For the microhardness test, thirty cylindrical specimens (6 mm× 8 mm) (n= 10) were fabricated to assess the microhardness, top and bottom surfaces were tested using Vicker Hardness test. The results were analyized with a one-way ANOVA test, the post-hoc comparisons were examined in Tukey test. Results: Abrasive Resistance results, Surefil one (9.52gr) and Beautifil bulk (4.16gr) showed an increase in weight after brushing, while Filtek one bulkfill (-0.85gr) showed a decrease in weight.Microhardness test results, Beautifil bulk showed the highest number of VH (74.83) followed by Surefil one (70.61) and Filtek one bulkfill (62.95). Conclusion: Beautifil bulk was more resistant to abrasion in comparison to Surefil one self-adhesive and One bulk fill. The great weight loss was observed in One bulk fill. Great weight gain was observed in Surefil one self-adhesive. Beautifil bulk showed the highest VH number compare to Surefil one self-adhesive and One bulk fill. Filtek one bulk fill showed low resistance and low hardness number.